Design of Magnetic Fluid-Enhanced Optical Fiber Polarization Filter - Haixu Chen; Lianzhen Zhang; Xin Ding (Micromachines)
In this paper, we demonstrated a method of filling the air holes of a photonic crystal fiber (PCF), coated with gold film, with magnetic fluid (MF) to enhance the Surface Plasmon Resonance (SPR). The simulation results show that at the wavelength of 1260–1675 nm, the minimum loss coefficient of the y-polarization mode is 4.7 times that before filling with MF, and the x-polarization mode is 0.45 times greater. Then, based on this method, we designed a polarizing filter with a core diameter of 9 µm. The numerical simulation results indicate that it not only maintains the same core diameter as the single-mode fiber, but also has a larger bandwidth and a higher extinction ratio (ER). Additionally, we can optimize its ER at a specific wavelength by adjusting the magnetic field.